Impact of Organizational Climate on Knowledge-Sharing Behavior: An Empirical Study in Minimarkets - Sri Raharso (Jurnal Bisnis dan Kewirausahaan, 2021)
This empirical research aims to identify the relationship between organizational climate and knowledge sharing behavior. Also, this study uses knowledge sharing intentions as a mediator between these two variables. The survey was conducted incidentally on 403 minimarket employees in eight districts/cities in West Java. Factor analysis was employed to purify research variables. To evaluate the research model, multiple regression analysis was used. The results of the factor analysis on organizational climate resulted in two factors, fairness and affiliation. Fairness and affiliation constructs have a positive and significant effect on knowledge sharing intention. Knowledge sharing intention also has a positive and significant effect on knowledge sharing behavior.